Islam and Environmental: The Role of Generation Z Students in Sustainable Campus Initiatives - Fauziah Astuti; Nadia Indah Safhira; Cucu Surahman (Universitas Islam Negeri (UIN) Mataram, 2025)
Indonesia, as one of the world’s largest waste producers, faces significant environmental challenges stemming from inadequate waste management, threatening both ecological systems and public health. This study investigates the role of Muslim Generation Z students in adopting zero-waste practices at a university in Bandung, examining how Islamic ethical principles influence their environmental awareness, attitudes, and participation. The study employed a quantitative survey method using a Likert-scale questionnaire and analyzed data from 40 respondents through descriptive statistical techniques. Results indicate that Generation Z students possess relatively high environmental awareness and demonstrate a positive alignment between zero-waste principles and their religious values, particularly the Islamic concept of khilafah (stewardship). Nevertheless, significant barriers remain in fully adopting zero-waste practices, including insufficient campus infrastructure, limited practical knowledge, and sociocultural challenges. The study recommends enhancing facilities, developing targeted educational programs, and involving religious leaders to strengthen environmental ethics among students.